Nitric Oxide/cGMP Signaling Pathway Protects RAW264 Cells Against Nitric Oxide-Induced Apoptosis by Inhibiting the Activation of p38 Mitogen-Activated Protein Kinase - Yoshioka Yasuhiro; Yamamuro Akiko; Keun-A Sadaaki (Elsevier, 2006)
Abstract.: Nitric oxide (NO) induces apoptosis in various cells lines, while activation of the NO/cGMP signaling pathway prevents apoptosis induced by diverse stimuli, including NO. Here, we report the cytoprotective mechanisms of the NO/cGMP signaling pathway against NO-induced apoptosis in a mouse macrophage-like cell line, RAW264. Treatment with sodium nitroprusside (SNP), an NO donor, at a high-toxic concentration (4 mM) stimulated the N-terminal conformational change of Bax and its translocation to mitochondria followed by cytochrome c release and nuclear fragmentation in RAW264 cells. These changes of Bax were attenuated by pretreatment with SNP at a low-nontoxic concentration (100 µM) or dibutyryl cGMP (DBcGMP), a cell-permeable cGMP analogue. SB203580, a p38 mitogen-activated protein kinase (MAP kinase) inhibitor, blocked the effects of 4 mM SNP on Bax translocation and cell viability. Treatment with 4 mM SNP activated p38 MAP kinase and this effect was prevented by pretreatment with 100 µM SNP or DBcGMP. These findings suggest that the NO/cGMP signaling pathway inhibits NO-induced apoptosis of macrophages by suppressing the p38 MAP kinase activation, which results in N-terminal conformational change of Bax and its translocation to mitochondria. Keywords:: nitric oxide, cGMP, Bax, p38 mitogen-activated protein kinase, RAW264 cell